2020
DOI: 10.3928/01477447-20191031-07
|View full text |Cite
|
Sign up to set email alerts
|

Sterility of 3D-Printed Orthopedic Implants Using Fused Deposition Modeling

Abstract: The use of 3-dimensional (3D) printing in orthopedics is developing rapidly and impacting the areas of preoperative planning, surgical guides, and simulation. As this technology continues to improve, the greatest impact of 3D printing may be in low- and middle-income countries where surgical items are in short supply. This study investigated sterility of 3D-printed ankle fracture fixation plates and cortical screws. The hypothesis was that the process of heated extrusion in fused deposition modeling printing w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
8
0
1
Order By: Relevance
“…Thus, it is important to have a clear understanding of the clinical value of 3D printing and potential limitations. The review article aims to provide an overview of 3D printed models in medical applications, specifically focusing its value in cardiovascular disease since its clinical applications in orthopaedics and maxillofacial areas are well explored and confirmed in the literature [23][24][25]. Further to the commonly reported usefulness of 3D printed models, use of 3D printed models for developing optimal computed tomography (CT) scanning parameters in cardiovascular disease is discussed and future research directions are highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is important to have a clear understanding of the clinical value of 3D printing and potential limitations. The review article aims to provide an overview of 3D printed models in medical applications, specifically focusing its value in cardiovascular disease since its clinical applications in orthopaedics and maxillofacial areas are well explored and confirmed in the literature [23][24][25]. Further to the commonly reported usefulness of 3D printed models, use of 3D printed models for developing optimal computed tomography (CT) scanning parameters in cardiovascular disease is discussed and future research directions are highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Printing with partial internal filling (% infill ) is common in household printings because the process is faster and more economical by using less raw material. Neches et al 22 and Skelley et al 23 demonstrated efficient sterilization of PLA printed objects automatically by the high temperature generated for the melting of the material during the printing of the objects, including the interior of the parts (∼ 200°C), requiring no further processing. Aguardo-Maestro et al 24 compared autoclave, OE, and plasma gas methods in the sterilization of hollow printed objects after inoculating a bacteria suspension inside them, finding efficacy only in the first two methods.…”
Section: Discussionmentioning
confidence: 99%
“…A impressão com enchimento interno parcial (% de infill ) é comum nas impressões domiciliares pois o processo é mais rápido e econômico por utilizar menor quantidade de matéria-prima. Neches et al 22 , e Skelley et al 23 demonstraram esterilização eficiente dos objetos impressos em PLA automaticamente pela alta temperatura gerada para o derretimento do material durante a impressão dos objetos, incluindo o interior das peças (∼ 200°C), não necessitando de processamento complementar. Aguardo-Maestro et al 24 compararam os métodos autoclave, OE e gás plasma na esterilização dos objetos impressos de modo oco após inocular uma suspensão de bactérias no interior dos mesmos, constatando eficácia apenas nos dois primeiros.…”
Section: Discussionunclassified
“…Other authors also studied 3D printing as a sterilization method but with ABS as a raw material [ 56 , 57 ]. Kondor and colleagues successfully manufactured a surgical instrument kit where 90% of the parts taken directly after printing were determined to be sterile by biological tests [ 56 ].…”
Section: New Approaches and Alternativesmentioning
confidence: 99%
“…The sterility of 3D-printed ankle fracture fixation plates and cortical screws (using ABS) were therefore assessed using thioglycollate broth cultures at 24 h, 48 h, and 7 days. The sterility of 100% of all test samples and the bacterial growth in the positive control demonstrated an intrinsic sterilization process suitable for FDM 3D printing in future orthopaedic applications [ 57 ]. The “in vitro” environment of this study also limited the ability to generalize the results as being sterile and safe for long term orthopaedic implants.…”
Section: New Approaches and Alternativesmentioning
confidence: 99%